2011
DOI: 10.1055/s-0031-1272476
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic Ovarian Drilling for Clomiphene-Resistant Polycystic Ovary Syndrome

Abstract: Laparoscopic ovarian drilling (LOD) is an alternative to ovulation induction with gonadotropins for polycystic ovarian syndrome (PCOS) patients unresponsive to clomiphene. It is quick and easy to perform, although the number of punctures and energy doses has not been standardized. The mechanism of LOD is unclear, but it is likely mediated by a reduction in intraovarian androgen production. Serum luteinizing hormone and testosterone levels are rapidly normalized, and these changes are sustained over long-term f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(30 citation statements)
references
References 81 publications
0
29
0
Order By: Relevance
“…8 Postoperative serum concentrations of androstenedione and testosterone decreases at least for a time, and inhibin concentrations also decline. 9 Both changes are likely contributed to an associated increase in FSH levels and thus ovulation. On the other hand, the mechanism of action of gonadotropins is to induce ovulation, maintain and provoke optimum follicle growth via the controlled administration of FSH and LH.…”
Section: Introductionmentioning
confidence: 99%
“…8 Postoperative serum concentrations of androstenedione and testosterone decreases at least for a time, and inhibin concentrations also decline. 9 Both changes are likely contributed to an associated increase in FSH levels and thus ovulation. On the other hand, the mechanism of action of gonadotropins is to induce ovulation, maintain and provoke optimum follicle growth via the controlled administration of FSH and LH.…”
Section: Introductionmentioning
confidence: 99%
“…Polycystic ovarian syndrome is thought to occur in 5–10% of reproductively aged women, and surgical treatment with wedge resection or ovarian 'drilling' is the typical choice for anovulation, as opposed to clomiphene or human menopausal gonadotropins. 9 In women undergoing procedures for bilateral endometriomas, there is a low but definite risk of post-surgical POI, and menopause can then occur earlier than normal. 10 Comparable studies have reported an immediate decline in antral follicle counts and serum AMH levels after cystectomy, but a partial restoration is normally observed several months later.…”
mentioning
confidence: 99%
“…Today, this procedure is successful in creating a pregnancy in 84% of patients with PCOS-related infertility (125). LOD helps improve insulin resistance (126) and ovarian androgen production, as well as increase the SHBG levels (127). These improvements have been seen to last in long-term follow-ups in 54% of women 8-12 years after the procedure (128, 129).…”
Section: Current Research and Future Perspectivementioning
confidence: 99%